Taking advantage from phenotype variability in a local animal genetic resource: identification of genomic regions associated with the hairless phenotype in Casertana pigs. (19th April 2018) - Schiavo, G.; Bertolini, F.; Utzeri, V. J.; Ribani, A.; Geraci, C.; Santoro, L.; Óvilo, C.; Fernández, A. I.; Gallo, M.; Fontanesi, L.
Summary: Casertana is an endangered autochthonous pig breed (raised in south‐central Italy) that is considered to be the descendant of the influential Neapolitan pig population that was used to improve British breeds in the 19th century. Casertana pigs are characterized by a typical, almost complete, hairless phenotype, even though a few Casertana pigs are normal haired. In this work, using Illumina PorcineSNP60 BeadChip data, we carried out a genome‐wide association study and an F ST analysis with this breed by comparing animals showing the classical hairless phenotype ( n  =   81) versus pigs classified as haired ( n  =   15). Combining the results obtained with the two approaches, we identified two significant regions: one on porcine chromosome (SSC) 7 and one on SSC15. The SSC7 region contains the forkhead box N3 ( FOXN3 ) gene, the most plausible candidate gene of this region, considering that mutations in another gene of the same family ( forkhead box N1 ; Foxn1 or FOXN1 ) are responsible for the nude locus in rodents and alopecia in humans. Another potential candidate gene, rho guanine nucleotide exchange factor 10 ( ARHGEF10 ), is located in the SSC15 region. FOXN3 and ARHGEF10 have been detected as differentially expressed in androgenetic and senescent alopecia respectively. This study on an autochthonous pig breed contributes to shed some light on novel genes potentially involved in hair development and growth and demonstrates that local animal breeds can be valuable genetic resources for disclosing genetic factors affecting unique traits, taking advantage of phenotype variability segregating in small populations.